The Impact of Physical Activity on Negative Affect and Sleep Quality in Adolescents: Network Analysis - Zhang B; Gao J (Psychology Research and Behavior Management)
Bin Zhang,1 Jianwei Gao2 1Beijing Sport University, Beijing, 100084, People’s Republic of China; 2Zhejiang Normal University, Jinhua, 321004, People’s Republic of ChinaCorrespondence: Jianwei Gao, Zhejiang Normal University, No. 688 Yingbin Road, Jinhua, Zhejiang, People’s Republic of China, Email gjw@zjnu.cnBackground: Negative affect may trigger a variety of psychological and behavioral problems, while physical activity has been shown to reduce negative affect. However, the underlying mechanisms remain unclear. The aim of this study was to investigate the relationship between physical activity and negative affect, specially examining the role of sleep quality in the relationship.Methods: Cross-sectional design was adopted in this study. A total of 557 adolescents participated in the study, completing self-reported questionnaires on physical activity, sleep quality, and negative affect.Results: Sleep quality mediated the relationship between physical activity and negative affect. There was a positive correlation between “exercise” and “sleep quality” and a negative correlation between “sleep restfulness” and “feeling bored”.Conclusion: This study uncovered the underlying mechanism of physical activity associated with negative affect, offering significance for the prevention and intervention of depression and anxiety disorders.Keywords: physical activity, negative affect, sleep quality, network analysis, adolescents